Influence of Self-Pulsation on Atomization Characteristics of Gas-Centered Swirl Coaxial Injector - Jiang, Chuanjin; Xie, Yuan; Gao, Yuchao; Chu, Wei; Tong, Yiheng; Li, Xiuqian; Nie, Wansheng (Frontiers in Energy Research, 2021)
There is a lack of understanding of the spray characteristics of gas-centered swirl coaxial (GCSC) injectors during self-pulsation occurs. Therefore, the self-pulsation of a GCSC injector was investigated experimentally in this study. A back-lighting high-speed photography technique was used to capture unsteady spray features. A laser-based particle size analyzer (LPSA) was used to measure the size of the droplets in the spray. The effects of recess and gas-liquid ratio on spray self-pulsation were analyzed. It was found that the recess of the injector strongly determines the spray pattern. When spray self-pulsation occurs without recess, both the center and periphery of the spray oscillate. With an increase in the mass flow rate of the gas, the boundary between the center and the periphery of the spray becomes more noticeable. Meanwhile, small droplets in the spray center oscillate, with the periphery of the spray being characterized by a periodic "shoulder.” Under the same operating conditions but with a small recess (2 mm), the spray adheres to the injector faceplate. With a larger recess (7 mm), when spray self-pulsation occurs, the spray periodically forms "shoulder" and "neck,” similar to the behavior of self-pulsation in a liquid-centered coaxial injector. Therefore, it can be concluded that spray self-pulsation enhances atomization at the center of the spray to a certain extent. However, atomization becomes worse in the periphery with an oscillating spray.